Las vías anselmiana y ockhamista para razonar a Dios desde sí mismo (2015)
Although with different ontologies, logical, linguistic theories (particularly the use of suppositio) and radical differences to the problem of universals, Anselm and Ockham are presented as two medieval thinkers who use their reason to assist the faith, and therefore agree the intuition of the common basis. Anselm's argument uses the assumption semantics, the logical and material implication, to 'think the greatness of the greatest' and release the spirit to 'the greatest' which by definition points beyond, right in the heart and one who create, using the appelatio semantically. For Ockham, this comprehension does not prove the predicate "existence" to distinguish between "show" and "test" denies any proof of the existence of God and believes that the routes of movement, efficient and final causation, are irrelevant because they lack evidence and from faith. He then turns to test the assumption of personal language, for "God" is not intentional meta-linguistic sign.